Structure Constants of the Weyl Calculus - Deng, Wen (MATHEMATICA SCANDINAVICA, 2013)
We find some explicit bounds on the $\mathcal{L}(L^2)$-norm of pseudo-differential operators with symbols defined by a metric on the phase space. In particular, we prove that this norm depends only on the "structure constants" of the metric and a fixed semi-norm of the symbol. Analogous statements are made for the Fefferman-Phong inequality.